Antitumor Activity of Extract From the Sporoderm-Breaking Spore of Ganoderma lucidum: Restoration on Exhausted Cytotoxic T Cell With Gut Microbiota Remodeling - Su, Jiyan; Su, Lu; Li, Dan; Shuai, Ou; Zhang, Yifan; Liang, Huijia; Jiao, Chunwei; Xu, Zhanchi; Lai, Yong; Xie, Yizhen (Frontiers in Immunology, 2018)
As breast cancer is the leading cause of cancer-related deaths in women population worldwide, ongoing endeavor have been made for alternative regimens with improved efficacy but fewer adverse effects. Recently, active components from the spores of Ganoderma lucidum have attracted much attention for their versatile biological activities owing to the advance in sporoderm-breaking technology. Here, anticancer potential of an extract derived from the sporoderm-breaking spores of G. lucidum (ESG) was explored in a 4T1-breast cancer xenograft mice model. Results showed that ESG was able to suppress 4T1 tumor growth in vivo rather than in vitro. Flowcytometry analysis revealed that ESG could significantly increase both cytotoxic T cell (Tc) population and the ratio of Tc to helper T cell (Th) in peripheral blood of the tumor-bearing mouse; similar promotion on Tc was also found in tumor infiltrating lymphocyte. Moreover, ESG evidently down-regulated the two immune checkpoints, PD-1 (in the spleen) and CTLA-4 (in the tumor), suggesting that ESG could effectively restore the T cell-paradigm by recovering the exhausion status via suppressing the co-inhibitory checkpoints. By 16S rRNA gene sequence analysis on the fecal microbiota, it was found that ESG would remodeling the overall structure of the samples from tumor-bearing mice toward that of the normal counterparts, including 18 genera in 5 phyla, together with regulations on several genes that are responsible for signaling pathways involved in metabolism, cellular processes, and environmental information processing. Collectively, the present study demonstrated that ESG would serve as a natural anticancer adjuvant via a restoration on the exhausted Tc, highlighting important clinical implications for the treatment of breast cancer.